2021
DOI: 10.3390/s21072423
|View full text |Cite
|
Sign up to set email alerts
|

Information Extraction and Population Estimates of Settlements from Historic Corona Satellite Imagery in the 1960s

Abstract: The Corona satellite program was a historic reconnaissance mission which provided high spatial resolution panchromatic images during the Cold War era. Nevertheless, and despite the historic uniqueness and importance of the dataset, efforts to extract tangible information from this dataset have primarily focused on visual interpretation. More sophisticated approaches have been either hampered or unrealized, often justified by the primitive quality of this early satellite product. In the current study we attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Our results showed that except for present-day Russia and China, CORONA imagery was also commonly used in India and Nepal; the Middle East (Iraq, Iran and Syria); Northern and Western Africa (Egypt, Mali and Senegal); and Central and Eastern Europe (Poland and Romania) [26,28,30,[42][43][44][52][53][54][55][56][57][58]. Some of these countries (e.g., Poland and Romania) have good coverage of CORONA imagery due to the goals of the program and the importance of the countries during the Cold War era [59][60][61]. One of the reasons that probably pushed researchers to use CORONA in several countries listed here is the poor availability of comparable aerial data that are not easily accessible via online archives, although they exist [5]: for instance, aerial data for Poland acquired in the 1950s or the 1960s.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that except for present-day Russia and China, CORONA imagery was also commonly used in India and Nepal; the Middle East (Iraq, Iran and Syria); Northern and Western Africa (Egypt, Mali and Senegal); and Central and Eastern Europe (Poland and Romania) [26,28,30,[42][43][44][52][53][54][55][56][57][58]. Some of these countries (e.g., Poland and Romania) have good coverage of CORONA imagery due to the goals of the program and the importance of the countries during the Cold War era [59][60][61]. One of the reasons that probably pushed researchers to use CORONA in several countries listed here is the poor availability of comparable aerial data that are not easily accessible via online archives, although they exist [5]: for instance, aerial data for Poland acquired in the 1950s or the 1960s.…”
Section: Discussionmentioning
confidence: 99%
“…CORONA imagery has been used because it offers unique insights to monitor changes at a high resolution of approximately 2–4 ft (0.6–1.2 m) per pixel using images pertaining to the 1960s (Fekete, 2020). The effective utilization of declassified high‐resolution CORONA data, alongside modern high‐resolution imagery, has proven valuable in mapping temporal land use changes, particularly tracking changes in the agriculture sector (Casana, 2020; Hamp‐Adams, 2020; Maurer et al, 2019; Stratoulias & Grekousis, 2021). The GeoEye data obtained were already georeferenced, but to ensure spatial overlap among all datasets, it was necessary to georeference the images to a consistent projection system (Danielson & Gesch, 2011; Neteler & Mitasova, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…High‐resolution satellite data offer advantages over traditional methods in mapping and monitoring vegetation status and water balance due to their cost‐effectiveness, temporal resolution and wide geographical coverage (Peña‐Barragán et al, 2011). The utilization of declassified high‐resolution CORONA data, in conjunction with contemporary high‐resolution imagery, has proven effective in mapping temporal land use changes (Casana, 2020; Maurer et al, 2019), particularly in monitoring transformations in agricultural land use, including changes in irrigation practices (Hamp‐Adams, 2020; Stratoulias & Grekousis, 2021). Furthermore, these types of analysis are augmented with the use of cloud‐based platforms, such as G EE, as they enable advanced analysis and processing of geospatial data at a planetary scale with extensive collection of satellite imagery and powerful computing capabilities (Orimoloye et al, 2021; Tamiminia et al, 2020; Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, agricultural land abandonment or rural depopulation in Bulgaria has not been studied from a remote sensing perspective, if we leave aside our preliminary work [22,23] and a follow-up study inspired and shaped by our work to a more considerable extent than it has been mentioned in acknowledgement [24]. These studies were also limited to their early satellite imagery.…”
Section: Introductionmentioning
confidence: 99%